Effects of Carboxyl or Amino Group Modified InP/ZnS Nanoparticles Toward Simulated Lung Surfactant Membrane - Wang, Juan; Feng, Shun; Liu, Jie; Liu, Rui-Lin (Frontiers in Bioengineering and Biotechnology, 2021)
Quantum dots (QDs) as a promising optical probe have been widely used for in vivo biomedical imaging; especially enormous efforts recently have focused on the potential toxicity of QDs to the human body. The toxicological effects of the representative InP/ZnS QDs as a cadmium-free emitter are still in the early stage and have not been fully unveiled. In this study, the DPPC/DPPG mixed monolayer was used to simulate the lung surfactant monolayer. The InP/ZnS-COOH QDs and InP/ZnS-NH2 QDs were introduced to simulate the lung surfactant membrane’s environment in the presence of InP/ZnS QDs. The effects of InP/ZnS QDs on the surface behavior, elastic modulus, and stability of DPPC/DPPG mixed monolayer were explored by the surface pressure-mean molecular area isotherms and surface pressure-time curves. The images observed by Brewster angle microscope and atomic force microscope showed that the InP/ZnS QDs affected the morphology of the monolayer. The results further demonstrated that the InP/ZnS QDs coated with different surface groups can obviously adjust the mean molecular area, elastic modulus, stability, and microstructure of DPPC/DPPG mixed monolayer. Overall, this work provided useful information for in-depth understanding of the effects of the −COOH or −NH2 group coated InP/ZnS QDs on the surface of lung surfactant membrane, which will help scientists to further study the physiological toxicity of InP/ZnS QDs to lung health.